A = 2016 x 2016
B = 2018 x 2014
A = 2016 x ( 2014 +2 )
A= 2016 x 2014 + 2016 x 2
B = 2018 x 2014
B = ( 2016 + 2 ) x 2014
B = 2016 x 2014 + 2014 x 2
Vì 2016 x 2014 = 2016 x 2014, mà 2016 x 2 > 2014 x 2
Vậy A > B
Ta có: b= 2018.2014 = (2016+2)(2016-2)= 20162 - 4 < 20162= 2016.2016=a
Ta có :
A = 2016 x 2016 = 2016 x ( 2018 - 2 ) = 2016 x 2018 - 2016 x 2
B = 2018 x 2014 = 2018 x ( 2018 - 4 ) = 2018 x 2018 - 2018 x 4
Vì 2016 x 2018 < 2018 x 2018 ; 2016 x 2 < 2018 x 4
=> A > B
A=2016.2016=2016.(2014+2)
=2016.2014+2.2016
B=2018.2014=(2016+2).2014
=2016.2014+2.2014
Vì 2016.2014=2016.2014 và 2.2016>2.2014
=>2016.2016 > 2018.2014
=> A > B